Water-soluble host–guest complexes between fullerenes and a sugar-functionalized tribenzotriquinacene assembling to microspheres - Liu, Si-Yuan; Wang, Xin-Rui; Li, Man-Ping; Xu, Wen-Rong; Kuck, Dietmar (Beilstein Journal of Organic Chemistry, 2020)
A sugar-functionalized water-soluble tribenzotriquinacene derivative bearing six glucose residues, TBTQ-(OG)6, was synthesized and its interaction with C60 and C70-fullerene in co-organic solvents and aqueous solution was investigated by fluorescence spectroscopy and ultraviolet-visible spectroscopy. The association stoichiometry of the complexes TBTQ-(OG)6 with C60 and TBTQ-(OG)6 with C70 was found to be 1:1 with binding constants of Ka = (1.50 ± 0.10) × 105 M−1 and Ka = (2.20 ± 0.16) × 105 M−1, respectively. The binding affinity between TBTQ-(OG)6 and C60 was further verified by Raman spectroscopy. The geometry of the complex of TBTQ-(OG)6 with C60 deduced from DFT calculations indicates that the driving force of the complexation is mainly due to the hydrophobic effect and to host–guest π–π interactions. Hydrophobic surface simulations showed that TBTQ-(OG)6 and C60 forms an amphiphilic supramolecular host–guest complex, which further assembles to microspheres with diameters of 0.3–3.5 μm, as determined by scanning electron microscopy.
Keywords: fullerenes; host–guest systems; microspheres; supramolecular chemistry; tribenzotriquinacene

(untitled) - Dawn, A.; Shiraki, T.; Ichikawa, H.; Takada, A.; Takahashi, Y.; Tsuchiya, Y.; Lien, L. T. N.; Shinkai, S. (J. Am. Chem. Soc., 2012)

(untitled) - Kishi, N.; Akita, M.; Yoshizawa, M. (Angew. Chem., Int. Ed., 2014)

(untitled) - Jia, F.; Li, D.-H.; Yang, T.-L.; Yang, L.-P.; Dang, L.; Jiang, W. (Chem. Commun., 2017)

(untitled) - Sun, W.; Wang, Y.; Ma, L.; Zheng, L.; Fang, W.; Chen, X.; Jiang, H. (J. Org. Chem., 2018)

(untitled) - Takeda, M.; Hiroto, S.; Yokoi, H.; Lee, S.; Kim, D.; Shinokubo, H. (J. Am. Chem. Soc., 2018)

Calixarenes and Beyond - Georghiou, P. E. (Calixarenes and Fullerenes, 2016)

(untitled) - Sygula, A. (Synlett, 2016)

(untitled) - Yanney, M.; Fronczek, F. R.; Sygula, A. (Angew. Chem., 2015)

(untitled) - García-Calvo, V.; Cuevas, J. V.; Barbero, H.; Ferrero, S.; Álvarez, C. M.; González, J. A.; Díaz de Greñu, B.; García-Calvo, J.; Torroba, T. (Org. Lett., 2019)

(untitled) - Lampart, S.; Roch, L. M.; Dutta, A. K.; Wang, Y.; Warshamanage, R.; Finke, A. D.; Linden, A.; Baldridge, K. K.; Siegel, J. S. (Angew. Chem., 2016)

(untitled) - Ikeda, A.; Ishikawa, M.; Aono, R.; Kikuchi, J.-i.; Akiyama, M.; Shinoda, W. (J. Org. Chem., 2013)

(untitled) - Mieda, S.; Ikeda, A.; Shigeri, Y.; Shinoda, W. (J. Phys. Chem. C, 2014)

(untitled) - Zhang, W.; Gong, X.; Liu, C.; Piao, Y.; Sun, Y.; Diao, G. (J. Mater. Chem. B, 2014)

(untitled) - Huerta, E.; Serapian, S. A.; Santos, E.; Cequier, E.; Bo, C.; de Mendoza, J. (Chem. – Eur. J., 2016)

(untitled) - Li, M.-J.; Huang, C.-H.; Lai, C.-C.; Chiu, S.-H. (Org. Lett., 2012)

(untitled) - Feng, L.-J.; Li, H.; Chen, Q.; Han, B.-H. (RSC Adv., 2013)

(untitled) - Ferrero, S.; Barbero, H.; Miguel, D.; García-Rodríguez, R.; Álvarez, C. M. (J. Org. Chem., 2019)

(untitled) - Yuan, K.; Guo, Y.-J.; Zhao, X. (J. Phys. Chem. C, 2015)

(untitled) - Cui, S.; Huang, Q.; Wang, J.; Jia, H.; Huang, P.; Wang, S.; Du, P. (Org. Lett., 2019)

(untitled) - Lu, X.; Gopalakrishna, T. Y.; Han, Y.; Ni, Y.; Zou, Y.; Wu, J. (J. Am. Chem. Soc., 2019)

(untitled) - Kuck, D. (Angew. Chem., Int. Ed. Engl., 1984)
Angew. Chem. 1984, 96, 515–516. doi:10.1002/ange.19840960725

(untitled) - Kuck, D. (Chem. Rev., 2006)

(untitled) - Tellenbröker, J.; Kuck, D. (Beilstein J. Org. Chem., 2011)

(untitled) - Li, Z.-M.; Tan, Y.; Ma, Y.-P.; Cao, X.-P.; Chow, H.-F.; Kuck, D. (J. Org. Chem., 2020)

(untitled) - Bredenkötter, B.; Henne, S.; Volkmer, D. (Chem. – Eur. J., 2007)

(untitled) - Bredenkötter, B.; Grzywa, M.; Alaghemandi, M.; Schmid, R.; Herrebout, W.; Bultinck, P.; Volkmer, D. (Chem. – Eur. J., 2014)

(untitled) - Henne, S.; Bredenkötter, B.; Alaghemandi, M.; Bureekaew, S.; Schmid, R.; Volkmer, D. (ChemPhysChem, 2014)

(untitled) - Henne, S.; Bredenkötter, B.; Dehghan Baghi, A. A.; Schmid, R.; Volkmer, D. (Dalton Trans., 2012)

(untitled) - Georghiou, P. E.; Dawe, L. N.; Tran, H.-A.; Strübe, J.; Neumann, B.; Stammler, H.-G.; Kuck, D. (J. Org. Chem., 2008)

(untitled) - Wang, T.; Li, Z.-Y.; Xie, A.-L.; Yao, X.-J.; Cao, X.-P.; Kuck, D. (J. Org. Chem., 2011)

(untitled) - Vile, J.; Carta, M.; Bezzu, C. G.; McKeown, N. B. (Polym. Chem., 2011)

(untitled) - Ng, C.-F.; Chow, H.-F.; Kuck, D.; Mak, T. C. W. (Cryst. Growth Des., 2017)

(untitled) - Greatorex, S.; Vincent, K. B.; Baldansuren, A.; McInnes, E. J. L.; Patmore, N. J.; Sproules, S.; Halcrow, M. A. (Chem. Commun., 2019)

(untitled) - Nakamura, E.; Isobe, H. (Acc. Chem. Res., 2003)

(untitled) - Strom, T. A.; Durdagi, S.; Ersoz, S. S.; Salmas, R. E.; Supuran, C. T.; Barron, A. R. (J. Pept. Sci., 2015)

(untitled) - Dondoni, A.; Marra, A. (Chem. Rev., 2010)

(untitled) - Yu, G.; Ma, Y.; Han, C.; Yao, Y.; Tang, G.; Mao, Z.; Gao, C.; Huang, F. (J. Am. Chem. Soc., 2013)

(untitled) - Lai, C.-H.; Hütter, J.; Hsu, C.-W.; Tanaka, H.; Varela-Aramburu, S.; De Cola, L.; Lepenies, B.; Seeberger, P. H. (Nano Lett., 2016)

(untitled) - García-Viñuales, S.; Delso, I.; Merino, P.; Tejero, T. (Synthesis, 2016)

(untitled) - Yang, F.; Chen, Q.; Cheng, Q.-Y.; Yan, C.-G.; Han, B.-H. (J. Org. Chem., 2012)

(untitled) - Li, H.; Chen, Q.; Han, B.-H. (New J. Chem., 2016)

(untitled) - Li, H.; Chen, Q.; Schönbeck, C.; Han, B.-H. (RSC Adv., 2015)

(untitled) - Kuck, D.; Heitkamp, S.; Letzel, M.; Ahmed, I.; Krohn, K. (Eur. J. Mass Spectrom., 2018)

(untitled) - Kuck, D.; Heitkamp, S.; Sproß, J.; Letzel, M. C.; Ahmed, I.; Krohn, K.; Parker, R. G.; Wang, Y.; Robbins, V. J.; Ames, W. M.; Schettler, P. D.; Hark, R. R. (Int. J. Mass Spectrom., 2015)

(untitled) - Halder, A.; Bhatt, S.; Nayak, S. K.; Chattopadhyay, S.; Bhattacharya, S. (Spectrochim. Acta, Part A, 2011)

(untitled) - Wolffs, M.; Hoeben, F. J. M.; Beckers, E. H. A.; Schenning, A. P. H. J.; Meijer, E. W. (J. Am. Chem. Soc., 2005)

(untitled) - Yu, G.; Zhao, R.; Wu, D.; Zhang, F.; Shao, L.; Zhou, J.; Yang, J.; Tang, G.; Chen, X.; Huang, F. (Polym. Chem., 2016)

(untitled) - Zhang, S.-Q.; Liu, Z.-Y.; Fu, W.-F.; Liu, F.; Wang, C.-M.; Sheng, C.-Q.; Wang, Y.-F.; Deng, K.; Zeng, Q.-D.; Shu, L.-J.; Wan, J.-H.; Chen, H.-Z.; et al. (ACS Nano, 2017)

(untitled) - Das, R. S.; Agrawal, Y. K. (Vib. Spectrosc., 2011)

(untitled) - Ferrari, A. C.; Basko, D. M. (Nat. Nanotechnol., 2013)

(untitled) - Ma, Y.; Zhang, X.; Cheng, Y.; Chen, X.; Li, Y.; Zhang, A. (New J. Chem., 2018)

Molclus Program, Version 1.7 (Tian Lu)

MOPAC2016 (Stewart Computational Chemistry)

(untitled) - Neese, F. (Wiley Interdiscip. Rev.: Comput. Mol. Sci., 2012)

(untitled) - Janiak, C. (J. Chem. Soc., Dalton Trans., 2000)